Analisis Pengaruh Corporate Governance dan Fraud Terhadap Pemilihan Auditor - Destin Alfianika Maharani (Universitas Sarjanawiyata Tamansiswa, 2019)
The research purpose is to know: 1). Influence of corporate governance to auditor choice, 2). Influence of fraud to auditor choice. The population of this research is a manufacturing company listed on the Indonesia Stock Exchange for the period 2013 to 2017. Determination of the sample in this study is using purposive sampling. The test equipment used in this study is using Eviews version 10. Logistic regression test results show that the independent variables (corporate and fraud) and control variables (firm size and profitability) simultaneously affect the dependent variable (auditor choice) by 29.31%. Meanwhile, the remaining 70.69% shows that the auditor choice variable is influenced by other variables not included in this research. Partially, corporate governance variables have a negative effect on the selection of auditors where corporate governance in this study has a coefficient of -2.742212 and a probability value of 0.0000. Fraud variables have a negative effect on the selection of auditors where fraud has a coefficient of -0.485367 and a probability value of 0.0066.